RISK FACTORS FOR EARLY WEANING AMONG BABIES FOLLOWED-UP IN A BABY-FRIENDLY PRIMARY CARE UNIT IN ISTANBUL - (:unkn) unknown (NOBEL ILAC, 2011)
Objective: This study aims to explore the breast-feeding profiles and the factors that affect breast-feeding and weaning attitudes among mothers of 0-12 month old babies in a baby-friendly primary care unit. Material and Method: The study was conducted in a Mother and Child Health Centre in Istanbul in May-October 2006. All 364 mothers who were registered in the health centre were enrolled. A total of 358 mothers were included in the study. Results: The frequencies of breastfeeding initiation and of breastfeeding within the first hour were 98.9% and 62.3% respectively. Among the babies older than 6 months (n=200), 52.5% were weaned before 6 months. Pacifier use (OR: 3.01, 95% CI: 1.35-6.69), being preterm (OR: 3.36, 95% CI: 1.04-10.79), having a job (OR: 2.83, 95% CI: 1.14-7.04) or smoking (OR: 2.27, 95% CI: 1.01-5.14) were found to be risk factors for early weaning. Conclusion: Although the frequency of initiating breastfeeding is very high, the continuation duration is below the World Health Organization (WHO)'s recommendations. Physicians and other health workers should strongly recommend against smoking during prenatal and postnatal visits. Physicians should not support pacifiers, until we have sufficient data to support its benefits. In order to increase the duration of breast feeding, health professionals should focus on preterm babies, smoking or working mothers.
Keywords: Breast-feeding; weaning; bottle-feeding; primary health care; infant; post-natal care; prenatal care; BREAST-FEEDING DURATION; PACIFIER USE; INFANTS; MOTHERS; SMOKING; HEALTH